To calculate the Gibbs free energy change G for the reaction, we can use the following equation:G = G products - G reactants First, we need to find the Gibbs free energy of the products and reactants. Since Gf H2 and Gf O2 are both 0 kJ/mol, we only need to consider the Gibbs free energy of formation for H2O.For the reactants, we have 2 moles of H2O:G reactants = 2 * Gf H2O = 2 * -237.13 kJ/mol = -474.26 kJ/molFor the products, we have 2 moles of H2 and 1 mole of O2, but their Gf values are 0, so:G products = 2 * Gf H2 + Gf O2 = 2 * 0 kJ/mol + 0 kJ/mol = 0 kJ/molNow, we can calculate the Gibbs free energy change for the reaction:G = G products - G reactants = 0 kJ/mol - -474.26 kJ/mol = 474.26 kJ/molThe Gibbs free energy change for the reaction 2H2O l 2H2 g + O2 g at 298 K is 474.26 kJ/mol.